Complete chloroplast genome of Holboellia grandiflora Réaubourg (Lardizabalaceae), a plant with an edible fruit. Issue 6 (3rd June 2022) - Li, Yan; Chang, Qinxiang; Zhang, Caijuan; Li, Huimin; Xia, Pengguo
Abstract: Holboellia grandiflora Réaubourg (Lardizabalaceae) is an evergreen twining perennial woody vine. To our knowledge, this is the first report on the complete chloroplast genome sequence of H. grandiflora . The complete chloroplast genome sequence was 157, 811 bp in length and contained a large single-copy region of 86, 554 bp and a small single-copy region of 18, 975 bp. A pair of inverted repeats of 26, 141 bp were included. It contained 130 genes, comprising 37 transfer RNA genes, and eight ribosomal RNA genes, as well as 85 coding sequences (CDSs). The GC content of the complete chloroplast genome sequence was 38.7%. The phylogenetic tree showed a close relationship among the three species of Holboellia (H. grandiflora, H. angustifolia, and H. latifolia ). These findings provide a reference for phylogenetic relationships and assessment of the genetic structure of the Lardizabalaceae family.